Comparative Evaluation of Antibacterial Efficacy of Commercially Available Rhamnosus Derived Therapeutic Agent Against Cariogenic Microorganism - Ranjan, Dr. Manish (Asian Journal of Pharmaceutics (AJP), 2025)
This study was designed to evaluate and compare the effectiveness of probiotics, synbiotics, and CHX 0.2%-against the Streptococcus mutans and Streptococcus salivarius, which are considered the most important targets in the pathways of causation that lead to dentistry-carious lesions. Materials and Methods: Pure cultures of S. mutans ATCC 25175 and S. salivarius ATCC 25975 were grown on Muller-Hinton agar and tested at 10⁶ CFU/mL bacterial inoculum. Assessing anti-bacterial properties was done through the assessment of the zone of inhibition (ZOI). Tooth surface swabs samples were evaluated on Mutans Sanguis Agar, with confluent colonies counted after 24-48 hours for biofilm assessment. Results: The highest ZOI produced by the CHX 0.2% was for S. mutans (25 ± 1.8 mm) followed by probiotics (18 ± 1 mm) and synbiotics (12 ± 0 mm). S. salivarius showed corresponding values of ZOI 24.3 ± 2.1 mm for CHX 0.2% and 16.6 ± 1.2 mm for probiotics and 13 ± 1 mm for synbiotics. One-way ANOVA explained that there is a statistically significant difference among groups (p < 0.05). It was stated in the biofilm assay that no growth was recorded for CHX 0.2% and synbiotics, while growth was recorded from the probiotics measured at 10⁸ CFU/mL. Conclusion: CHX 0.2% revealed the strongest antibioactivity example, but probiotics and synbiotics demonstrated mild effects. Therefore, future studies are needed to ascertain the applicability of probiotics and synbiotics as alternative agents for caries prevention, though thus far they have proven to be promising measures